1967
DOI: 10.1126/science.156.3779.1231
|View full text |Cite
|
Sign up to set email alerts
|

Living Relative of the Microfossil Kakabekia

Abstract: A living, ammonia-obligate, umbellate form, similar to the Precambrian microfossil Kakabekia umbellata Barghoorn, has been isolated from two soil specimens collected at Harlech, Wales. This organism is amenable to culture on agar and in broth. The two soil specimens are similar in that they differ from a typical clay loam in high content of carbon, hydrogen, and organic nitrogen and low levels of sodium, potassium, and titanium. In all other constituents, such as calcium, magnesium, and iron, they are quite di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1968
1968
1999
1999

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The intracellular (cytoplasmic) ammonium concentration, which must be exceeded before toxicity is observed, is very high in some organisms (e.g. Siegel & Giumarro, 1966;Siegel et aL, 1967;Siegel, Nathan, & Roberts, 1968;Sayeed & Kenny, 1978;Hoddinott, Reid & Ingledew, 1978;Raven, 1980), A problem in all considerations of toxicity and metabolism of ammonium is that it is not clear whether the active species is NH3 or NH^, Work on other phototrophs which attempts to distinguish between NH3 and NH^*^ as the major species crossing the plasmalemma includes that of Barr, Koh & Ryan (1974) and of Loppert (1979), in addition to the work of Walker et al ( 1979a) and Walker et al (1979b) on Chara corallina which was discussed in the Introduction. Barr et al (1974) showed that the ammonium distribution between the vacuole of Nitella elavata and the bathing medium could be explained in terms of vacuolar and external pH values and passive NH3 transport, with i' NH3 ^^^ ^^^ plasmalemma plus tonoplast of 4,4,10"^ cm s-', With the relatively high (2,5-14 mmol m^^) concentrations of NH3 in the bathing medium in these experiments, it is likely that diffusive NH3 entry could supply both assimilatory and storage demands for ammonia; any NH^ uniporter present in the plasmalemma would presumably be subject to feedback inhibition under these conditions (cf.…”
Section: (2) Nhj and Nh^ Transport And Distributionmentioning
confidence: 99%
“…The intracellular (cytoplasmic) ammonium concentration, which must be exceeded before toxicity is observed, is very high in some organisms (e.g. Siegel & Giumarro, 1966;Siegel et aL, 1967;Siegel, Nathan, & Roberts, 1968;Sayeed & Kenny, 1978;Hoddinott, Reid & Ingledew, 1978;Raven, 1980), A problem in all considerations of toxicity and metabolism of ammonium is that it is not clear whether the active species is NH3 or NH^, Work on other phototrophs which attempts to distinguish between NH3 and NH^*^ as the major species crossing the plasmalemma includes that of Barr, Koh & Ryan (1974) and of Loppert (1979), in addition to the work of Walker et al ( 1979a) and Walker et al (1979b) on Chara corallina which was discussed in the Introduction. Barr et al (1974) showed that the ammonium distribution between the vacuole of Nitella elavata and the bathing medium could be explained in terms of vacuolar and external pH values and passive NH3 transport, with i' NH3 ^^^ ^^^ plasmalemma plus tonoplast of 4,4,10"^ cm s-', With the relatively high (2,5-14 mmol m^^) concentrations of NH3 in the bathing medium in these experiments, it is likely that diffusive NH3 entry could supply both assimilatory and storage demands for ammonia; any NH^ uniporter present in the plasmalemma would presumably be subject to feedback inhibition under these conditions (cf.…”
Section: (2) Nhj and Nh^ Transport And Distributionmentioning
confidence: 99%
“…Kakabekia is another small form with a spherical body to which is attached a stalked, umbrella-like structure. A recent paper by Siegel et al (1967) reporting modern Kakabekia-like organisms from soil samples must be accepted with caution. One cannot help questioning the identical form of these two types of "organisms."…”
Section: Precambrian Paleobotanymentioning
confidence: 99%